Tuning magnetoresistive and magnetocaloric properties via grain boundaries engineering in granular manganites. Issue 81 (15th August 2016) - Mohamed, Abd El-Moez A.; Mohamed, Mohamed A.; Vega, V.; Hernando, B.; Ahmed, A. M.
Abstract : The effect of interface size on the relative cooling power and magnetoresistive properties of La0.7 Ba0.3 MnO3 compounds is investigated. Abstract : In this work, we investigate the effect of interface size on the electrical, magnetoresistive, magnetic and magnetocaloric properties of the La0.7 Ba0.3 MnO3 (LBMO) manganite compound. This is done by introducing different sizes of secondary phases of Ni and Ag (Ni powder, Ni nanowires, Ag oxide powder and Ag nanoparticles) to the LBMO compound, forming inhomogeneous systems of LBMO/Ni and LBMO/Ag composites. X-Ray diffraction patterns reveal the interaction lack between Ni & Ag interfaces and LBMO compound through the coexistence of their characteristic peaks. This suggests the segregation of these interfaces between LBMO grains, leading to a change in the boundary resistance that is found to be an interface-size-dependent change. Accordingly, the transport properties of LBMO are changed, where, the resistivity increases and the metal–semiconductor transition temperature decreases with the introduced interfaces. The change in grain boundary resistance enhances the magnetoresistive properties during the promotion of the spin carrier tunnelling process. For instance, the room temperature low field magnetoresistance of the LBMO compound is enhanced from −1.23% to −4.35, −5.25 and −7.9% with the introduction of Ni powder, Ag nanoparticles and Ag oxide powder interfaces, respectively. The dc thermal magnetization measurements show a constant value of the LBMO Curie temperature ( T c ) with the introduced interfaces that may be attributed to the complete interaction lack. However, a small decrease is registered in the T c value of Ni nanowires doped LBMO composite, that may be due to the incomplete interaction lack in this composite. Moreover, the magnetocaloric properties of the LBMO compound show a notable enhancement with the introduced interfaces, where its relative cooling power is enhanced from 44 J kg −1 to 107, 167, 92 and 94 J kg −1 with the introduction of Ni powder, Ni nanowires, Ag oxide and Ag nanoparticle interfaces, respectively, at a 3 T applied magnetic field.